Determination of serum neutralizing antibodies reveals important difference in quality of antibodies against pertussis toxin in children after infection. Issue 13 (26th March 2021) - Zhang, Yuxiao; Li, Yarong; Chen, Zhiyun; Liu, Xiaoguai; Peng, Xiaokang; He, Qiushui
Highlights: A CHO cell assay was developed to measure PT neutralizing antibodies (PTNAs). A correlation between serum titers of PTNAs and anti-PT IgG levels was observed. Patients with same level of anti-PT IgG antibodies can have different PTNAs. Determination of PTNAs is important for assessment of functional antibodies. Abstract: Objectives: To determine neutralizing antibodies to pertussis toxin (PTNAs) in children with suspected pertussis and to compare results of PTNAs and anti-PT IgG antibodies. Methods: 172 hospitalized children with suspected pertussis were included. Pertussis was confirmed by culture, PCR and/or serology. PTNAs were determined by Chinese hamster ovary (CHO) cell assay. Results: A correlation between titers of PTNAs and anti-PT IgG levels was noticed in 172 patients (Spearman R = 0.68, P < 0.001). Subjects with same concentrations of anti-PT IgG antibodies could have different titers of PTNAs and the maximum difference observed reached to 1024 times in ELISA-confirmed patients. Moreover, subjects with same titers of PTNAs could have different concentrations of anti-PT IgG antibodies. Conclusions: Our results indicated that in some children high concentrations of anti-PT IgG antibodies do not always mean effective PTNAs induced after infection, stressing the importance of detecting PTNAs after infection and vaccination. Clinical trial registry: Not applicable.